HUBUNGAN EFEKTIFITAS TEKNIK MASSAGE DAN TEKNIK RELAKSASI DENGAN PENGURANGAN NYERI PUNGGUNG PADA KEHAMILAN TRIMESTER III DI KLINIK PRATAMA MEDIKA KELUARGA CIPINANG MUARA JAKARTA TIMUR TAHUN 2017 - Dewi Kurniati; Anni Suciawati; Dea Aulia (Universitas Nasional, 2017)
During pregnancy, women would changed whether anatomy , physiology and psychology causing discomfort during pregnancy. One discomfort often experienced pregnant women is back pain (Varney, dkk) 2006. Mantle suggested that 50 % pregnant women in survey in england and scandinavia reported suffer pain a significant and 70 % women in australia a back injury at some stage pregnancy , for that physical exercise and posture are specific can help pregnant women in adapting to change in physical on the body during pregnancy (Brayshaw, 2009) .dari the univariat done in this research suggests intervention effective against pregnant mother of a back injury, To a decrease in the pain scale back pain there are 6 pregnant women ( 23 % ) mild pain, 18 pregnant women ( 69 % ) pain medium and 2 pregnant women ( 8 % ) pain weight. Concluded that engineering massage and techniques of relaxation Concluded that engineering therapist and techniques of relaxation effective in lowering pain delivery in pregnant women a trimester III at the clinic pratama medika family cipinang muara jakarta.Was recommended to the village midwife to be more promoted programs class pregnant women in which there are gymnastic pregnant for alleviating gripes patients to pain back.